Identifikasi Kelimpahan dan Karakteristik Fisik Mikroplastik pada Pengolahan Air Lindi Tempat Pengelolaan Sampah Terpadu Bantargebang - Putri, Rahayu Nabila; Sari, Gina Lova; Amanah, Nadia (Universitas Tanjungpura, 2025)
The growth of plastic consumption in Indonesia can reduce the increase in microplastic pollution in various environments, including in leachate in the Final Processing Site (TPA). Bantargebang TPST is a large-scale waste management site that has high potential for microplastic contamination. Microplastics are plastic particles measuring